The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/cb.1737
|View full text |Cite
|
Sign up to set email alerts
|

It takes time to tango: The relative importance of values versus traits in consumer brand relationships

Abstract: Brand managers have several options in their quest to connect their brands with consumers. They may stress functional brand attributes and benefits, their brand's personality traits, or their brand's values (the human values attached to the brand). Which of these is most important to consumers is an open question, however. This article proposes that values may take on increased importance over time, as long‐term relationships (in general) require more than just getting the job done (functional aspect) or a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 64 publications
3
23
2
Order By: Relevance
“…The connection between values and involvement was examined by O'Cass (2001) with the result that the involvement with an object is higher when it is strongly connected to the consumer's values. As for comparing values with personality traits, a study by Voorn et al (2018, p. 537) found that values were the stronger factors in a consumer–brand relationship. They played a greater role in future decisions than traits, which is an indication of the importance of values for purchasing decisions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between values and involvement was examined by O'Cass (2001) with the result that the involvement with an object is higher when it is strongly connected to the consumer's values. As for comparing values with personality traits, a study by Voorn et al (2018, p. 537) found that values were the stronger factors in a consumer–brand relationship. They played a greater role in future decisions than traits, which is an indication of the importance of values for purchasing decisions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Individuals attempt to align their behavior with their values and tend to purchase products that match these values (Voorn et al, 2018). Therefore, values can contribute to consumer loyalty and prevent the consumer from switching brands (Voorn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The longer the relationship with a brand lasts, the more important human values will become. This was demonstrated in a recent study conducted by Voorn et al (2018), which showed that when products or services are used over a longer period of time, the importance of values does increase in comparison to products or services that are only used for a shorter period of time. And as brand values play an important role when consumers select products or services they can identify with (Sihvonen, 2019;Stockburger-Sauer et al, 2012), it can be expected that the longer the relationship lasts, it will also increase the level of brand identification.…”
Section: Influence Of Usage Durationmentioning
confidence: 87%
“…This is in particular the case when it is not possible to assess a service, not even after it has been purchased, unless you are an expert yourself, as is the case for credence services such as insurance, bank services or notary office assistance (Galetzka, Verhoeven, & Pruyn, 2006). As services pose more risk and uncertainty to consumers than products due to their lack of tangibility and veritable grounds to evaluate them, they may base their choice of services more on brand values than when they select products (Groeppel-Klein & Kobel, 2018;Mort & Rose, 2004;Voorn et al, 2018, Zhang & Bloemer, 2008. Compatibility in the importance awarded to values will decrease the perceived risk in such cases (Arts, Frambach, & Bijmolt, 2011;Rogers, 2003).…”
Section: Difference Between Products and Servicesmentioning
confidence: 99%
See 1 more Smart Citation